2015
DOI: 10.1186/s40413-015-0061-4
|View full text |Cite
|
Sign up to set email alerts
|

Severity of allergic rhinitis and asthma development in children

Abstract: Allergic rhinitis (AR) is a relevant risk factor for the development of asthma in children. We recruited a cohort of 104 children with AR and re-evaluated them after 5 years. We considered the ARIA classification. All patients, who had moderate to severe persistent AR at baseline, developed asthma symptoms. These results strongly indicate that the severity of AR may be an important factor that increases the risk of asthma development in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
2
9
1
2
Order By: Relevance
“…In a previous Portuguese nationwide and population-based study, current wheezing showed a strong association with moderate to severe-persistent AR in preschool children 27. Another prospective study on children aged 6–12 years reported that the severity and duration of AR were significantly associated with asthma,28 which is comparable to our findings.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous Portuguese nationwide and population-based study, current wheezing showed a strong association with moderate to severe-persistent AR in preschool children 27. Another prospective study on children aged 6–12 years reported that the severity and duration of AR were significantly associated with asthma,28 which is comparable to our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, in Italy 24 patients (23.08 %) of 104 examined children with allergic rhinitis had a mild persistent course; this fact is consistent with our data [15]. In Spain, the moderate course of allergic rhinitis had 63% of the examined children, which is 12% less than our data, but the hypersensitivity to domestic dust mites was registered with a higher frequency and was equal to 61.9 % [16].…”
Section: Resultssupporting
confidence: 91%
“…Few former studies in this emerging scientific field, have reported that children with asthma and AR exhibit poorer asthma control and higher risk of exacerbations, impaired life quality and increased healthcare cost compared to individuals without AR ( 5 , 31 , 32 ). Of note, nearly 80% of children with asthma exhibit concomitant AR, and ~40% with AR exhibit concomitant asthma ( 5 , 6 , 33 ).…”
Section: Discussionmentioning
confidence: 99%